A double recombinant herpes virus of turkeys for the protection of chickens against Newcastle, infectious laryngotracheitis and Marek's diseases. Issue 1 (2nd January 2019) - Gergen, Linda; Cook, Stephanie; Ledesma, Brooke; Cress, Wade; Higuchi, Deb; Counts, Diane; Cruz-Coy, Julio; Crouch, Colin; Davis, Phillip; Tarpey, Ian; Morsey, M.
ABSTRACT: A double recombinant strain of herpes virus of turkeys (HVT) was constructed that contains the fusion (F) gene from Newcastle disease virus (NDV) and the gD plus gI genes from infectious laryngotracheitis virus (ILTV) inserted into a non-essential region of the HVT genome. Expression of the F protein was controlled by a human cytomegalovirus promoter, whereas expression of gD plus gI was driven by an ILTV promoter. The double recombinant vaccine virus (HVT-NDV-ILT) was fully stable genetically and phenotypically following extended passage in cell culture and infection of chickens. Safety of the vaccine virus was confirmed by overdose and backpassage studies in specific-pathogen-free chickens. Chickens vaccinated with a single dose of HVT-NDV-ILT administered by the in ovo route were highly protected from challenge with the velogenic NDV (GB Texas), ILTV (LT 96-3) and Marek's disease virus (GA 5) strains (97%, 94% and 97%, respectively). Similarly, chickens vaccinated with a single dose by subcutaneous (SC) route at 1 day of age were highly protected from challenge with the same three viruses (100%, 100%, and 88%, respectively). The protection level of a single dose given by in ovo or SC route against challenge with a virulent Marek's disease virus strain demonstrates that insertion of multiple genes from two different pathogens within the HVT genome had no adverse effect on the capacity of HVT to protect against Marek's disease. These results demonstrate that HVT-NDV-ILT is a safe and efficacious vaccine for simultaneous control of NDV, ILTV and Marek's diseases.